2017
DOI: 10.1097/rti.0000000000000248
|View full text |Cite
|
Sign up to set email alerts
|

Left Ventricular Myocardial Fibrosis, Atrophy, and Impaired Contractility in Patients With Pulmonary Arterial Hypertension and a Preserved Left Ventricular Function

Abstract: In patients with PAH, changes in T1 and ECV support the hypothesis of LV myocardial fibrosis and atrophy with a consecutively impaired contractility despite a preserved LV function, possibly due to longstanding PAH-associated LV underfilling.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
34
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(35 citation statements)
references
References 38 publications
1
34
0
Order By: Relevance
“…17,18 Fat-water separation sequences such as Dixon provide volumetric quantification of fat. [19][20][21][22][23] Tereshchenko et al demonstrated that interatrial septum fat, measured in the interatrial septum using a fat-water separated sequence, was associated with AF risk. 24 LA-epicardial fat shows a quite nonuniform spatial distribution.…”
mentioning
confidence: 99%
“…17,18 Fat-water separation sequences such as Dixon provide volumetric quantification of fat. [19][20][21][22][23] Tereshchenko et al demonstrated that interatrial septum fat, measured in the interatrial septum using a fat-water separated sequence, was associated with AF risk. 24 LA-epicardial fat shows a quite nonuniform spatial distribution.…”
mentioning
confidence: 99%
“…investigated LV myocardial changes associated with PAH by strain analysis and mapping techniques. 107 Both native T1 and ECV were higher in patients with PAH and LV longitudinal strain was impaired (–18 vs. –23, P < 0.01). However, there was no change in LVEF.…”
Section: Myocardial Tissue Characterization and Myocardial Perfusion mentioning
confidence: 89%
“…In contrast to systemic hypertension without LV hypertrophy, pulmonary hypertension was found to be associated with increased native LV and RV myocardial T1 and ECV regardless of the underlying disease etiology [88][89][90][91][92]. Increased native T1 values at the ventricular insertion points (Fig.…”
Section: Eccentric Left Ventricular Hypertrophymentioning
confidence: 99%
“…In a recent study, Caspar et al [99] reported various etiologies of intracardiac masses including myxoma, recent and old thrombi, hemangioma, lymphoma, lipoma, fibroelastoma, rhabdomyoma, caseous calcification, and metastasis. Besides it's supportive nature to standard CMR characterization [90], it remains to date unclear if and to what extend myocardial T1 mapping will contribute to the differentiation of cardiac masses. Taking into account the heterogeneous nature of cardiac masses (Fig.…”
Section: Cardiac Tumors and Massesmentioning
confidence: 99%
See 1 more Smart Citation